Understanding the effects of transcranial direct current stimulation on the neurovascular unit: a narrative review - Lewis, Aidan; Rattray, Ben; Flood, Andrew (Frontiers in Neuroscience, 2025)
Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation technique that has demonstrated promise both for treating diverse clinical conditions and for enhancing brain function in healthy adults. Despite increasing popularity, the precise physiological mechanisms underlying its effects remain poorly defined, contributing to inconsistent findings. This review synthesises current evidence for both acute and enduring effects of tDCS across the complete neurovascular unit, encompassing neurons, astrocytes, oligodendrocytes, microglia, the blood–brain barrier, metabolic pathways, and immune responses. We review recent transcriptomic, proteomic, and metabolomic studies which reveal that tDCS induces coordinated molecular changes, including modulation of genes involved in inflammation, neurogenesis, calcium signalling, mitochondrial metabolism, and synaptic plasticity proteins. We emphasise significant gaps in current literature, particularly the limited consideration given to astrocytes and oligodendrocytes, despite their known importance in activity-dependent plasticity. We conclude that the neurovascular unit represents an integrative and complex target of tDCS, suggesting that comprehensive modulation of these components may better explain observed changes in cognitive, behavioural, and neuropsychological outcomes. Future research should move beyond a neuron-centric perspective, embracing a more integrative framework that considers interactions amongst all elements of the neurovascular unit. Such a holistic approach will enhance our understanding of how tDCS exerts its effects, thereby improving its clinical utility.